2020
DOI: 10.1039/c9tc06854f
|View full text |Cite
|
Sign up to set email alerts
|

Highly conductive n-type CH3NH3PbI3 single crystals doped with bismuth donors

Abstract: Highly conductive n-type CH3NH3PbI3 single crystals are grown by bismuth doping and the optical fingerprints of bismuth induced donors in CH3NH3PbI3 perovskites are identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 50 publications
4
30
0
Order By: Relevance
“…have performed the Hall effect to identify the conductivity type of the Bi‐doped MAPbI 3 single crystal. [ 29 ] We also performed a Hall effect test for the single crystal with different metal electrode, and results are shown in Table 1 . In the Hall effect test, four Au electrodes with the size of 2 mm × 2 mm are necessary to ensure good contact between the sample and the instrument.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…have performed the Hall effect to identify the conductivity type of the Bi‐doped MAPbI 3 single crystal. [ 29 ] We also performed a Hall effect test for the single crystal with different metal electrode, and results are shown in Table 1 . In the Hall effect test, four Au electrodes with the size of 2 mm × 2 mm are necessary to ensure good contact between the sample and the instrument.…”
Section: Resultsmentioning
confidence: 99%
“…Previous literatures have reported that the intrinsic conductivity of single crystal is slightly P‐type, and our test results agree with them. [ 29,30 ] After adding an Au electrode among the Au test electrodes, the measured Hall coefficient is still positive, and the measured Hall coefficient and mobility values have increased significantly. We consider that the intrinsic P‐type conductivity of the MAPbI 3 single crystal is enhanced due to the addition of the Au electrode.…”
Section: Resultsmentioning
confidence: 99%
“…We calculate the Urbach energies as 79.5, 95.6, and 60.4 meV for Cs 3 Bi 2 Cl 9 SC, Cs 3 Bi 2 Br 9 SC, and Cs 3 Bi 2 I 9 SC, respectively. Here, we observe that in bismuth-based perovskite single crystals, the Urbach energy is higher than that of pure lead-based and Bi-doped lead halide perovskite single crystals. It was reported earlier that after bismuth doping in lead halide perovskite single crystals, the Urbach energy enhanced because Bi creates localized energy states. , The higher value of Urbach energy suggests the more structural disorder and enhancement of localized state density in our Bi-based lead-free single crystals. Moreover, the high degree of structural disorder in Bi-based single crystals corresponds to a large amount of vacancies for the mobile ions.…”
mentioning
confidence: 99%
“…The properties of conventional semiconductor could be adjusted by impurity doping, similarly, heterovalent metals doping into PSCs is an efficient way to change the electrical and optical properties [17][18][19][20][21]. MAPbCl 3 is proved to be a n − type semiconductor [12], while doping Bi 3+ into MAPbX 3 would move Femi level close to conduction band [22,23]. Inspired by the above work, we suppose to fabricate n − -n + photo-diodes based on n −type MAPbCl 3 single crystal substrate with n + -type Bidoped MAPbCl 3 epitaxial layer.…”
Section: Introductionmentioning
confidence: 99%